Peningkatan HOTs dan Reduksi Miskonsepsi Pembelajaran Fisika dengan Mengkomparasi Inquiry Learning dan Problem Solving: Studi Meta-Analisis - Aziz Kurniawan (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
The role of teachers in the learning process has a very important role to play in producing the learning process. However, the reality in the field of teachers has not been able to provide the existing experience in the learning process so it can cause them to engage in HOTs and there are still misconceptions, especially physics subjects where students are just the theory. To learn about research by comparing Inquiry Learning with Problem Solving in order to increase HOTs and reduce physics misconceptions. This study reported 21 articles that included 10 Inquiry Studies and 11 Problem Solving. The result of this research is that Fhitung> Ftabel is 4,355> 3.55, and a probability value of 0.029 <0.05 which means a comparison of Learning about Problem Solving that can result in HOTs and misconceptions.